Espectroscopia de Estrelas Be nos aglomerados NGC 4755 e NGC 6530 - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
One of the main theories to explain the Be phenomenon is that they are hot stars with rotation speed close to the critical limit, ejecting matter and forming a gaseous disk around. Its geometry and kinematics is still a controversial subject. Those objects present H® line in emission among other phenomena. In this work are present observations of hot stars in young open clusters and the detection of Be stars. The study of Be stars in open clusters is a matter of interest because these objects keep the initial signatures of their initial formation. Most of Be stars known in open clusters were identified inside the Milky Way Galaxy, but not all were observed. Most of the observations concentrate on seeking the characteristics lines in emission for stars with low magnitude. As a consequence the complete scenario of incidence of Be stars in open clusters is still uncertain, what incentives its observation. In this work, we studied thirty two stars of the spectral type B, from NGC 4755 and NGC 6530 stellar clusters. As a first step we accomplished an analysis of the stars that present the Be phenomenon. Than, we estimate physical parameters of B and Be stars using the lines of HeI 4471 and MgII 4481 Å. We also accomplished a comparison among the vseni values calculated by several methods including the AMOEBA algorithm and other two methods elaborated using the IDL platform. For high-speeds (» 300 Km/s), there is a superestimative of the FWHM method for both clusters. But for low-speeds, there is consistence between values of vseni obtained with the FWHM method and AMOEBA.
Keywords: espectroscopia estelar; estrelas Be; linhas de Balmer; rotação estelar; stellar spectroscopy; Be stars; Balmer lines; stellar rotation; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA